Safety and efficacy of intravenous bimagrumab in inclusion body myositis (RESILIENT): a randomised, double-blind, placebo-controlled phase 2b trial. Issue 9 (September 2019) - Hanna, Michael G; Badrising, Umesh A; Benveniste, Olivier; Lloyd, Thomas E; Needham, Merrilee; Chinoy, Hector; Aoki, Masashi; Machado, Pedro M; Liang, Christina; Reardon, Katrina A; de Visser, Marianne; Ascherman, Dana P; et al.
Summary: Background: Inclusion body myositis is an idiopathic inflammatory myopathy and the most common myopathy affecting people older than 50 years. To date, there are no effective drug treatments. We aimed to assess the safety, efficacy, and tolerability of bimagrumab—a fully human monoclonal antibody—in individuals with inclusion body myositis. Methods: We did a multicentre, double-blind, placebo-controlled study (RESILIENT) at 38 academic clinical sites in Australia, Europe, Japan, and the USA. Individuals (aged 36–85 years) were eligible for the study if they met modified 2010 Medical Research Council criteria for inclusion body myositis. We randomly assigned participants (1:1:1:1) using a blocked randomisation schedule (block size of four) to either bimagrumab (10 mg/kg, 3 mg/kg, or 1 mg/kg) or placebo matched in appearance to bimagrumab, administered as intravenous infusions every 4 weeks for at least 48 weeks. All study participants, the funder, investigators, site personnel, and people doing assessments were masked to treatment assignment. The primary outcome measure was 6-min walking distance (6MWD), which was assessed at week 52 in the primary analysis population and analysed by intention-to-treat principles. We used a multivariate normal repeated measures model to analyse data for 6MWD. Safety was assessed by recording adverse events and by electrocardiography, echocardiography, haematological testing, urinalysis, and blood chemistry. This trial is registered with ClinicalTrials.gov, number NCT01925209; this report represents the final analysis. Findings: Between Sept 26, 2013, and Jan 6, 2016, 251 participants were enrolled to the study, of whom 63 were assigned to each bimagrumab group and 62 were allocated to the placebo group. At week 52, 6MWD change from baseline did not differ between any bimagrumab dose and placebo (least squares mean treatment difference for bimagrumab 10 mg/kg group, 17·6 m, SE 14·3, 99% CI –19·6 to 54·8; p=0·22; for 3 mg/kg group, 18·6 m, 14·2, –18·2 to 55·4; p=0·19; and for 1 mg/kg group, –1·3 m, 14·1, –38·0 to 35·4; p=0·93). 63 (100%) participants in each bimagrumab group and 61 (98%) of 62 in the placebo group had at least one adverse event. Falls were the most frequent adverse event (48 [76%] in the bimagrumab 10 mg/kg group, 55 [87%] in the 3 mg/kg group, 54 [86%] in the 1 mg/kg group, and 52 [84%] in the placebo group). The most frequently reported adverse events with bimagrumab were muscle spasms (32 [51%] in the bimagrumab 10 mg/kg group, 43 [68%] in the 3 mg/kg group, 25 [40%] in the 1 mg/kg group, and 13 [21%] in the placebo group) and diarrhoea (33 [52%], 28 [44%], 20 [32%], and 11 [18%], respectively). Adverse events leading to discontinuation were reported in four (6%) participants in each bimagrumab group compared with one (2%) participant in the placebo group. At least one serious adverse event was reported by 21 (33%) participants in the 10 mg/kg group, 11 (17%) in the 3 mg/kg group, 20 (32%) in the 1 mg/kg group, and 20 (32%) in the placebo group. No significant adverse cardiac effects were recorded on electrocardiography or echocardiography. Two deaths were reported during the study, one attributable to subendocardial myocardial infarction (secondary to gastrointestinal bleeding after an intentional overdose of concomitant sedatives and antidepressants) and one attributable to lung adenocarcinoma. Neither death was considered by the investigator to be related to bimagrumab. Interpretation: Bimagrumab showed a good safety profile, relative to placebo, in individuals with inclusion body myositis but did not improve 6MWD. The strengths of our study are that, to the best of our knowledge, it is the largest randomised controlled trial done in people with inclusion body myositis, and it provides important natural history data over 12 months. Funding: Novartis Pharma.